Transforming Islamic Education through a Massive Open Online Course Model Based on Open Islamic Educational Resources - Moh Ali; Riyanto Riyanto; Wahyono Wahyono; Neila Najmi Aulia (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
In the digital era, Islamic education faces significant challenges in ensuring broad and inclusive access to quality learning. This study aims to design, analyze, and implement a Mass Open Online Course (MOOC) based on Open Islamic Educational Resources (OIER) as a strategy to transform Islamic education. Using a qualitative Research and Development (R&D) approach, data were collected through in-depth interviews with experts in Islamic education and educational technology, observations of existing MOOC platforms, and document analysis. The findings indicate that OIER-based MOOCs play a substantial role in advancing the transformation of Islamic education by improving accessibility, learning quality, and institutional collaboration. Successful implementation is supported by three key pillars: inclusive technology design, a curriculum grounded in Islamic values, and the active involvement of stakeholders, including educators, learners, and the educational community. The developed MOOC integrates classical Islamic disciplines such as fiqh, aqidah, and Islamic history with 21st-century competencies, including critical thinking, digital literacy, and global communication, thus preserving the essence of Islamic values ​​while enhancing contemporary relevance. Furthermore, the integration of OIER into the MOOC platform expands global access to Islamic educational resources, particularly for underserved communities, improves learning quality through interactive multimedia, and strengthens cross-institutional collaboration. Empirical results show an 18% increase in student understanding of the material after using the platform. Overall, this study concludes that OIER-based MOOCs have significant potential to transform Islamic education into a more inclusive, modern, and globally connected system without compromising its core values.